Astroclimate parameters of the Kyiv observatories - Rieznik, K.; Reshetnyk, V.M. (Advances in Astronomy and Space Physics, 2012)
Astroclimate parameters such as the atmospheric extinction, the night-sky brightness, and the seeing are studied using the observational data obtained at some Kyiv observatories. The first parameter is determined using the brief Bouguer method. The night-sky brightness is calculated using the images of standard stars in different filters. And the seeing is estimated basing on the FWHM of star profiles obtained during a set of observations at Kyiv observatories.